Comparative analysis of transmission of the word «曰» in kazakh, russian and english (based on the novel of pu songling «miss ying-ning, or the laughing girl»). - Nurzhayeva., A. M. (Journal of Oriental Studies, 2016)
In the article was carried out comparative analysis of word曰in Kazakh, Russian and English languages.The study conducted on translated novel «Miss Ying-Ning, or The laughing girl» of Chinese writer Pu Sunlin into the appropriate languages.